Konflikt palestyńsko-izraelski - Bunton, Martin (Wydawnictwo Uniwersytetu Łódzkiego, 2017)
Konflikt palestyńsko-izraelski to przystępne wyjaśnienie istoty rozgrywającego się współcześnie i silnie obecnego w mediach sporu międzynarodowego. Jakie były źródła i przebieg tego konfliktu? Gdzie leży jego sedno? Czy rozwiązanie dwupaństwowe jest możliwe do zrealizowania? Jak światowe mocarstwa rywalizowały o wpływy w regionie? The Palestinian-Israeli Conflict: A Very Short Introduction was originally published in English in 2013. This translation is published by arrangement with Oxford University Press. Wydawnictwo Uniwersytetu Łódzkiego is solely responsible for this translation from the original work and Oxford University Press shall have no liability for any errors, omissions or inaccuracies or ambiguities in such translation or for any losses caused by reliance thereon